A promising new tamarind selection-lakshamana : Linking biodiversity with livelihood - C Kanupirya (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
Tamarind is a well-known commodity of Indian cuisine having medicinal and industrial uses. It is a nutritious tree crop of widespread occurrence growing on marginal lands in semi-arid and sub-humid tropical climates of India, making it highly valuable in ensuring food security for rural poor. Given the great potential of this neglected and underutilized species to address global challenges such as hunger, poverty and climate change adaptation, there is a need to revisit research and development priorities in its favor and to develop strategies together with stakeholders to increase its utilization. In the present study, a survey was undertaken in Tumkur district of Karnataka to characterize the variability available in tamarind for pod and tree characters and identify superior trees using horticultural traits. A farmer’s tamarind selection “Lakshamana” emerged from participatory breeding having significantly better traits compared to local tamarind.